Penapisan Fitokimia Infusa Daun Thalassia hemprichii yang Berpotensi Sebagai Antimikroba - Suwarny Suwarny; Satriani Syarif; La Ode Alrin (Faculty of Science and Technology University Ibrahimy, 2024)
Thalassia hemprichii is a spermatophyte plant that grows in aquatic ecosystems. This plant is a type of seagrass widely distributed in the waters of Southeast Sulawesi and has long been utilized by coastal communities for various purposes, including traditional medicine. This study aims to conduct phytochemical screening of Thalassia hemprichii infusion from the waters of Tondonggeu, Southeast Sulawesi, and to assess its potential as a natural antimicrobial agent. The methods used include interviews with local communities to explore traditional knowledge about seagrass utilization, as well as phytochemical screening of Thalassia hemprichii leaf infusion. The interview results show that the Tondonggeu community utilizes various parts of the seagrass plant for medicinal purposes, including as a wound treatment, antidiarrheal, fever medicine, stomach ache remedy, and nutritional supplement. Phytochemical screening revealed the presence of alkaloids, terpenoids, saponins, tannins, and flavonoids in the T. hemprichii leaf infusion. These findings indicate a correlation between traditional uses and phytochemical content, supporting the potential of T. hemprichii as a natural antimicrobial source. This study concludes that Thalassia hemprichii has significant potential for further development as a source of natural medicine, especially in antimicrobial discovery. However, further research is needed to isolate specific active compounds and conduct clinical trials to validate its safety and efficacy. The utilization of T. hemprichii as a source of natural medicine must be balanced with conservation efforts to ensure the sustainability of this species and the seagrass ecosystem. Keywords: Thalassia hemprichii, phytochemical screening, antimicrobial